Seismogenic Faulting of the 2016 Mw 6.0 Hutubi Earthquake in the Northern Tien Shan Region: Constraints From Near-Field Borehole Strain Step Observations and Numerical Simulations - Li, Yujiang; Zhang, Huiping; Tang, Lei; Chen, Lianwang; Jing, Yan (Frontiers in Earth Science, 2020)
Constraining the seismotectonic faulting that occurred as a result of the 2016 Mw 6.0 Hutubi earthquake provides valuable information about the deformation in the northern Tien Shan region. However, due to the lack of surface rupturing and high quality near-field teleseismic data, the exact nature of the faulting remains controversial. In our study, we analyze the coseismic strain time series of the Mw 6.0 Hutubi earthquake using strain data collected from nearby borehole stations. The tensile and compressive coseismic strain steps account for most of the recorded borehole data in this region. Employing a numerical model that is based on elastic dislocation theory, we reproduce the observed tensile and compressive coseismic strain steps using source parameters that were generated through seismic wave inversion, seismic reflection data, and aftershock relocation. By conducting a comparative analysis between the predicted and observed coseismic strain steps, we study the seismogenic faulting of the Mw 6.0 Hutubi earthquake. The results indicate that when the source parameters are 292°/62°/80° (strike/dip/rake), the predicted tensile and compressive characteristics for 13/16 channels are consistent with the observational data. Based on these results, we infer that the seismogenic faulting, which is located near the Horgos-Manas-Tugulu fault, can be characterized as a high-angle blind back-thrust fault with a north-dipping fault plane. Providing constraints on the seismogenic faulting associated with the 2016 Mw 6.0 Hutubi earthquake also yields to understand the mechanism of the overall deformation pattern in the northern Tien Shan region.